2021
DOI: 10.1101/2021.08.24.21262475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of commercial anti-SARS-CoV-2 antibody assays and comparison of standardized titers in vaccinated healthcare workers

Abstract: With the availability of vaccines, commercial assays detecting anti-SARS-CoV-2 antibodies (Ab) evolved towards quantitative assays directed to the spike glycoprotein or its receptor binding domain (RBD). The main objective of the present study was to compare the Ab titers obtained with quantitative commercial binding Ab assays, after 1 dose (convalescent individuals) or 2 doses (naive individuals) of vaccine, in healthcare workers (HCW).Antibody titers were measured in 263 sera (from 150 HCW) with 5 quantitati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…The Abbott assay used in this study has a wide range of linear IgG(S-RBD) quantification, which has been shown to correlate with the level of neutralizing antibodies generated following natural infection or vaccination. The assay has been tested and validated against WHO international standard [14].…”
Section: Discussionmentioning
confidence: 99%
“…The Abbott assay used in this study has a wide range of linear IgG(S-RBD) quantification, which has been shown to correlate with the level of neutralizing antibodies generated following natural infection or vaccination. The assay has been tested and validated against WHO international standard [14].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an association between measured anti-RBD/S1 antibody titers and clinical protective effects against SARS-CoV-2 [27] . However, the measured antibody levels may differ depending on the methods and target antigen used in different immunoassays [28] , [29] , [30] . In our study, we used three different assays to measure the levels of anti-RBD/S1 antibodies and neutralizing ability following vaccination, which is one of the strengths of this study.…”
Section: Discussionmentioning
confidence: 99%
“…While they show seroconversion by all participants after the second dose and overall high qualitative correlation between the assays (kappa range 0.80–0.96), the fold difference in antibody levels ranged from 106-fold by the Elecsys anti-S total antibody electrochemiluminescent immunoassay (ECLIA; Roche Diagnostics) to 1.24-fold by the a nAb ELISA (SD Biosensor, South Korea), suggesting significant interassay measurement differences. More recently, Saker et al assessed vaccine responses across multiple commercially available semiquantitative serologic assays, where output values were converted to BAU/mL relative to the WHO IS SARS-CoV-2 antibody standard, using manufacturer-provided conversion factors ( 5 ). Using 255 sera from 150 HCWs fully vaccinated with the BNT162b2 or AZD1222 vaccines, they show that the mean difference in resulting BAU/mL values among four quantitative assays differed anywhere from 10.6% to 60.9% between assays.…”
Section: Immunity Following Sars-cov-2 Vaccinationmentioning
confidence: 99%
“…Also, while we have a plethora of serologic assays with Food and Drug Administration (FDA) Emergency Use Authorization (EUA), these assays were developed to assess prior SARS-CoV-2 infection status, not immunity status. These assays currently have limited cross-assay correlation and lack standardization, despite the availability of a World Health Organization (WHO) international standard for anti-SARS-CoV-2 antibodies, and the majority of the assays detect binding antibodies (bAb), not specifically nAbs ( 3 5 ). Here, we provide a brief status update regarding our current understanding of immunity to SARS-CoV-2, focusing on humoral immune responses, CoPs, and the application of currently available SARS-CoV-2 serologic tests to determine antibody levels and immunity.…”
Section: Introductionmentioning
confidence: 99%